Youth Violence: An Overview of Predictors, Counselling Interventions, and Future Directions - Leschied, Alan W.; Cummings, Anne L. (Canadian Journal of Counselling and Psychotherapy, 2007)
This special issue of the Canadian Journal of Counselling focuses on one of society's greatest challenges: youth violence. This article provides counsellors with a general overview of the major advances in understanding the etiology of youth violence, the highlights of promising counselling interventions, and the role of gender in addressing prevention and intervention efforts. There is much knowledge about factors that characterize high-risk violent youth, as well as intervention programs that can reduce the occurrence of violence. The authors suggest that the greatest challenge currently is program dissemination and the transfer of research knowledge on youth violence into counselling practice.